The year that was - Firdousi, Ishrat, 1954- (Dhaka : Bastu Prakashan, 1996)
Compilation of personal narratives of the 1971 Bangladesh revolution; includes accounts of the atrocities during the war.
Includes index.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Personal narratives; Bangladesh -- History -- Revolution, 1971 -- Atrocities